Reduced graphene oxide catalysts for efficient regeneration of cobalt-based redox electrolytes in dye-sensitized solar cells. (20th November 2016) - Giannouri, Maria; Bidikoudi, Maria; Pastrana-Martínez, Luisa M.; Silva, Adrián M.T.; Falaras, Polycarpos
Abstract: Efficient and low cost reduced graphene oxide (rGOV) is prepared by chemical reduction of graphene oxide (GO) using vitamin C. Detailed characterization by XRD, SEM and Raman techniques confirm the successful reduction of GO. Thin films of rGOV with various thickness are deposited by spin coating on FTO glass substrates and are used as counter electrodes (CEs) in dye-sensitized solar cells (DSCs) incorporating the organic sensitizer D35 dye and the Co(bpy)3 3+ /Co(bpy)3 2+ redox couple. These devices present high photocurrent density ( jsc ) and open-circuit voltage ( Voc ) values resulting in enhanced photovoltaic performance in comparison with the Pt catalyst. The novel rGOV electrodes constitute an excellent, low-cost and environmentally friendly alternative solution to the costly platinum-based cathodes.